Tooth powder for periodontal antibiosis and anti-inflammation and tooth remineralization and preparation method thereof
The tooth powder prepared by hydrogen-calcium silicon alloy multifunctional nanomaterials uses photothermal conversion and hydration reaction to solve the problems of inflammation treatment and teeth remineralization in periodontitis treatment, and achieves a daily non-invasive and non-drug-resistant high-efficiency treatment effect.
Patent Information
- Application Number
- CN202411877159.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve daily non-invasive inflammatory treatment and teeth remineralization in the treatment of periodontitis, and the abuse of antibiotics may lead to drug side effects and bacterial resistance.
Tooth powder is prepared by multifunctional nanomaterial of hydrogen release calcium silicon alloy, which destroys the bacterial membrane through photothermal conversion and releases hydrogen in contact with saliva or water, and coordinates the treatment of periodontal inflammation and promotes tooth remineralization.
It has achieved high H2 concentration in the lesions of periodontitis for a long time, effectively inhibited bacterial infection and treated periodontitis, and was not drug-resistant, able to repair enamel and realize remineralization of teeth.
Smart Images

Figure CN119700559A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oral care, and in particular relates to a tooth powder for periodontal antibacterial and anti-inflammatory treatment and tooth remineralization and a preparation method thereof. Background Art
[0002] Periodontitis is the second most common oral disease and the sixth most common disease in the world, with 11.2% of people worldwide suffering from severe periodontitis. It is a chronic inflammation caused by bacteria in dental plaque invading periodontal tissues, also known as destructive periodontal disease. Bacteria accumulate on the surface of teeth and roots, leading to destruction of periodontal supporting tissues, formation of periodontal pockets, loss of attachment and absorption of alveolar bone. If periodontitis is not promptly intervened and treated, it can eventually lead to tooth loss. In addition, increasing evidence shows that periodontitis is a high-risk factor for the onset of a variety of systemic diseases, and the longer it lasts, the higher the risk of oral and systemic diseases.
[0003] At present, mechanical operations such as debridement, flap surgery, bone grafting, and guided tissue regeneration are the main clinical methods. Mechanical actions usually not only bring pain, sensitivity and other adverse feelings to patients, but also make it difficult to completely remove the infection on the surface of irregularly shaped teeth, and easily lead to enamel loss; in addition, it also requires the use of a variety of antibiotics for auxiliary treatment to achieve oral disinfection or oral restoration of nutritional supplements and hormone management. Unfortunately, the abuse of antibiotics can easily lead to drug side effects and bacterial resistance, and they cannot directly promote tooth remineralization or repair. Therefore, it is extremely necessary and important to find a simple, effective, daily and non-invasive intervention measure to achieve the treatment and intervention of inflammation and tooth remineralization at the same time.
[0004] Remarkably, molecular hydrogen (H2) has been shown to be an emerging safe, effective, and sufficient broad-spectrum anti-inflammatory agent. The therapeutic mechanism of hydrogen refers to the fact that hydrogen penetrates biological membranes and selectively removes highly oxidative / toxic free radicals, such as hydroxyl radicals (·OH). In addition, previously reported routes of H2 anti-inflammatory administration mainly include inhaling hydrogen, drinking hydrogen water, and injecting physiological solutions of hydrides. Due to the low solubility and high dispersion of H2, high H2 concentrations cannot be achieved in the lesion site for a long time, resulting in limited anti-inflammatory effects; and it is impossible to effectively inhibit periodontitis caused by bacterial infection, and it is impossible to remineralize teeth eroded by bacteria. And due to the compensatory effect, hydrogen may induce more ROS production, but through Ca 2+ Signal transduction pathways regulate the transcription of certain genes, which can reduce oxidative stress damage and inhibit inflammatory cytokines. Therefore, how to design a suitable nanohydrogen generator to effectively achieve targeted and sustained release of hydrogen at the lesion site, while inhibiting bacterial infection, treating periodontitis and repairing teeth, is a key challenge.
[0005] At the same time, bioactive ceramics are widely used in hard tissue repair materials due to their excellent biocompatibility, cytocompatibility, low immunogenicity, osteoconductivity and osteoinductivity. In the normal oral environment, demineralized enamel can absorb Ca in saliva. 2+ Remineralization requires a large amount of Ca 2+ . And, Ca 2+ It can also balance oral microorganisms and stimulate the proliferation of gingival fibroblasts. 2+ The antibacterial properties of Ca are limited, especially in the complex oral environment of periodontitis. 2+ Bacteriostasis can only play an auxiliary role. Photothermal therapy (PTT) is a new clinical treatment strategy that converts light energy into heat energy through photothermal nanoparticles to achieve selective non-invasive local treatment. Among them, photothermal agents (PTA) have attracted great attention as alternative drugs to antibiotic treatment due to their low toxicity and side effects, high selectivity and non-drug resistance. However, how to design suitable nanoparticle photothermal agents to effectively improve the efficacy of PTT remains a key challenge. Summary of the invention
[0006] In view of the above defects or improvement needs of the prior art, the present invention aims to provide a multifunctional nanomaterial of hydrogen-releasing calcium-silicon alloy for treating periodontitis induced by pathogenic bacteria.
[0007] To achieve the above object, according to one aspect of the present invention, a method for preparing a tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization is provided, the method comprising the following steps:
[0008] S100: grinding Ca powder and Si powder and then calcining for the first time, naturally cooling, adding Si powder to the first calcined product, repeating the grinding step, and then calcining for the second time, wherein the grinding and calcining processes are both carried out under an inert gas protective atmosphere;
[0009] S200: After the second calcined product is cooled naturally, impurities are removed by washing, and then ball milled in a sealed environment for 100 minutes;
[0010] S300: After subjecting the ball milled product to ultrasonic and centrifugal treatment, the supernatant is collected and centrifuged again, and then dried to obtain tooth powder.
[0011] Furthermore, the mass ratio of the Ca powder to the Si powder is 10:7.
[0012] Furthermore, the mass of Si powder added to the first calcined product is 2.43 times the mass of the first calcined product.
[0013] Furthermore, the grinding step in S100 specifically includes: first grinding for 30 minutes, and then adding anhydrous ethanol and further grinding for 10 minutes.
[0014] Furthermore, the first calcination in S100 is calcined at 1000° C. for 5 minutes, and the second calcination is calcined at 1000° C. for 10 hours.
[0015] Furthermore, the sealing environment in S200 is liquid-sealed by adding anhydrous ethanol.
[0016] Furthermore, the ultrasonic and centrifugal treatment process of the ball milling product in S300 specifically includes: ultrasonicating the ball milling product in an ice bath for 1.5 hours, then centrifuging at 3000 rpm for 10 minutes, collecting the supernatant, and then centrifuging at 12000 rpm for 20 minutes.
[0017] Furthermore, the drying temperature in S300 is 50° C. and the drying time is 24 hours.
[0018] According to another aspect of the present invention, a tooth powder prepared according to the above method for periodontal antibacterial and anti-inflammatory and tooth remineralization is provided.
[0019] Furthermore, the tooth powder is nano-CaSi2 powder.
[0020] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0021] 1. The hydrogen-releasing calcium-silicon tooth powder material prepared by the present invention can destroy the bacterial membrane through photothermal conversion under the action of light; it can also react with oral saliva or water to release hydrogen through hydration, synergistically treating periodontal inflammation; and promote tissue recovery at the same time. In addition, the tooth powder can also repair tooth enamel to achieve tooth remineralization. Therefore, the hydrogen-releasing calcium-silicon material prepared by the present invention is expected to achieve multifunctional applications in the oral environment, that is, to achieve inflammation treatment of periodontal tissues, antibacterial and tooth remineralization through daily oral cleaning.
[0022] 2. The hydrogen-releasing calcium-silica tooth powder material prepared by the present invention is used to treat periodontitis induced by pathogenic bacteria. Compared with clinical surgical operation combined with antibiotic treatment, it is a simple, effective, daily non-invasive and non-resistant intervention measure. It can relieve periodontitis better than drinking hydrogen water. It can achieve high H2 concentration in the lesion site for a long time; and it can effectively intervene in inflammation caused by bacterial infection, and repair tooth bone loss caused by inflammation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM+EDS image of the tooth powder prepared in the embodiment of the present invention;
[0024] Figure 2 XRD spectrum of the tooth powder prepared in the embodiment of the present invention;
[0025] Figure 3 This is a diagram of system stability analysis (Zeta potential) of the tooth powder prepared in the embodiment of the present invention;
[0026] Figure 4 The ultraviolet-visible-near infrared (UV / VIS / NIR) absorption spectrum of the tooth powder prepared in the embodiment of the present invention;
[0027] Figure 5 This is a photothermal conversion performance evaluation diagram of the tooth powder prepared in an embodiment of the present invention;
[0028] Figure 6 , 7 8 are the HOK cell biocompatibility evaluation results of the tooth powder prepared in the embodiment of the present invention, wherein: Figure 6 For cell live-death staining images, Figure 7 , 8 The results are flow cytometry results;
[0029] Fig. 9 , 10 The bacterial test results of the tooth powder prepared in the embodiment of the present invention are as follows: Fig. 9 The bacterial plate coating process and SEM image. Fig.10 The colony counting results are shown in Figure 2.
[0030] Fig.11 This is a gas chromatography test chart of hydrogen production performance of the tooth powder prepared in an embodiment of the present invention;
[0031] Fig.12 This is an XPS graph of the hydrogen production reaction of the tooth powder prepared in the embodiment of the present invention;
[0032] Fig.13 This is an experimental diagram of the effect of electron capture on hydrogen production performance according to an embodiment of the present invention;
[0033] Fig.14 This is an electron paramagnetic resonance (EPR) diagram of an embodiment of the present invention;
[0034] Fig.15 , 16 is the simulation calculation result of the embodiment of the present invention, wherein, Fig.15 is the VMD visualization result of the electron transition process. Fig.16 VMD visualization results for hole-electron state analysis;
[0035] Fig.17 Cell experiment of the tooth powder prepared in the embodiment of the present invention - ROS and H2O2 expression morphology of each group of RAW264.7;
[0036] Fig.18Cell experiment of the tooth powder prepared in the embodiment of the present invention - CaSi2 induced the morphology of each group of RAW264.7;
[0037] Fig.19 This is a schematic diagram of the construction and treatment of a ligature-induced periodontitis model in mice according to an embodiment of the present invention;
[0038] Fig. 20 The photographs and micro-CT images of the alveolar bones of mice in the embodiments of the present invention are shown;
[0039] Fig.21 The alveolar bone resorption status and tissue analysis results of mice in the embodiment of the present invention;
[0040] Fig. 22 H&E staining and Masson staining of mouse alveolar bone in an embodiment of the present invention;
[0041] Fig.23 This is the immunohistochemical staining of the alveolar bone of mice in the embodiment of the present invention;
[0042] Fig.24 is the positive area ratio of various inflammatory-related factors in the alveolar bone of mice in the embodiment of the present invention;
[0043] Fig.25 The SEM images of human ex vivo teeth before and after acid erosion and after 1, 3, and 7 in vitro mineralization treatments of human ex vivo teeth with CaSi2 tooth powder in simulated oral saliva are shown in the embodiments of the present invention;
[0044] Fig.26 The At values of human teeth before and after acid erosion and after 1, 3, and 7 in vitro mineralization treatments of human teeth with CaSi2 tooth powder in simulated oral saliva according to the present invention are shown in FIG. Ca / At P picture. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0046] The present invention provides a method for preparing a tooth powder for periodontal antibacterial and anti-inflammatory effects and tooth remineralization, the method comprising the following steps:
[0047] 1. Mix Ca powder and Si powder in a mass ratio of 10:7, grind for 30 minutes under an inert gas atmosphere, add anhydrous ethanol and grind for 10 minutes, heat to 1000°C and calcine for 5 minutes under an inert gas atmosphere, cool naturally, add Si powder 2.43 times the mass of the calcined product to the calcined product, repeat the grinding steps, and then heat to 1000°C and calcine for 10 hours under an inert gas atmosphere;
[0048] 2. After the second calcination product is cooled naturally, it is washed with anhydrous ethanol to remove impurities, then transferred to a ball mill, and anhydrous ethanol is added for liquid sealing, and ball milled for 100 minutes;
[0049] 3. Ultrasonicate the ball-milled product in an ice bath for 1.5 h, then centrifuge at 3000 rpm for 10 min, collect the supernatant, centrifuge at 12000 rpm for 20 min, and then dry at 50°C for 24 h to obtain nano-CaSi2 tooth powder.
[0050] Example 1
[0051] The specific steps of preparing a tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization in this embodiment are as follows:
[0052] 10 parts by mass of Ca powder and 7 parts by mass of Si powder were ground in a mortar for 30 minutes under an Ar protective atmosphere to mix evenly. Subsequently, 1 mL of anhydrous ethanol was added to the mixture and further ground for 10 minutes. Then, the obtained mixture was transferred to a porcelain boat and heated for 5 minutes in a tube furnace heated at 1000 ° C under an argon atmosphere for calcination. After natural cooling, the product was taken out, Si powder with a mass ratio of 2.43:1 to the product was added, the grinding step was repeated, and the obtained mixture was transferred to a porcelain boat, and heated for 10 hours in a tube furnace heated at 1000 ° C under an argon atmosphere for calcination. After natural cooling, the product was taken out, impurities were washed off with anhydrous ethanol, transferred to a 100 ml tetrafluoroethylene ball mill, a certain amount of anhydrous ethanol was added for liquid sealing, and then 3 2 mm ball milling beads + 4 5 mm ball milling beads + 8 8 mm ball milling beads + 8 10 mm ball milling beads were added, and the ball mill speed was adjusted to 586 rpm, and ball milling was performed for 100 minutes. After obtaining the ball-milled sample, it was ultrasonicated in an ice bath for 1.5 h to remove large particles, the product was centrifuged at 3000 rpm for 10 min, the supernatant was collected, and then centrifuged at 12000 rpm for 20 min. Finally, it was dried at 50°C for 24 h to obtain a nano-CaSi2 powder sample.
[0053] In order to better understand the performance of the samples prepared in the above examples, they were tested and characterized, and the results are as follows:
[0054] 1. SEM+EDS test
[0055] The SEM+EDS of CaSi2 tooth powder is shown in the attached Figure 1 As shown. SEM images show that CaSi2 is a quasi-two-dimensional material with small particle size, large specific surface area, high reactivity and electron mobility, strong adsorption capacity and light absorption performance. EDS scanning results show that the total number of distribution maps meets the relative atomic mass ratio of calcium and silicon of 1:2, and the results are consistent with the expected composition results during the material preparation process.
[0056] 2. XRD test
[0057] The XRD spectrum of CaSi2 tooth powder is shown in the attached figure. Figure 2 As shown, its chemical composition and crystal structure were further clearly confirmed, and the synthesized material was consistent with the PDF card of CaSi2, indicating that the synthesis method of CaSi2 was effective.
[0058] 3. System stability analysis (Zeta potential)
[0059] To evaluate the stability of the material in different oral environments, the Zeta potential in periodontitis saliva (pH = 6.85 ± 0.11), normal oral environment (pH = 6.6-7.1), and periodontitis gingival crevicular fluid (pH = 8.1 ± 0.57) was tested. Figure 3 As shown, since CaSi2 has a higher absolute value in different pH systems, its stability (solubility and dispersibility) is good.
[0060] 4. Light absorption performance evaluation
[0061] Good photothermal stability and photothermal conversion efficiency are one of the key characteristics of PTA. The UV / VIS / NIR absorption spectrum shows the optical absorption characteristics of the material in the range of 200-1000nm. Figure 4 It can be seen that CaSi2 has excellent light absorption performance in the visible light-infrared light wavelength range.
[0062] 5. Photothermal conversion performance evaluation
[0063] In order to further study the photothermal conversion performance of CaSi2, we systematically evaluated the photothermal conversion efficiency of CaSi2 in water dispersions of different concentrations in a short period of time under a xenon lamp (300W) simulating natural light. At the same time, the temperature rise of deionized water was obtained as a blank control under the same conditions, and the room temperature was 25℃. The experimental results are shown in Figure 5 As shown, it can be seen that CaSi2 has good photothermal conversion efficiency and concentration dependence.
[0064] 6. HOK cell biocompatibility evaluation (live and dead staining, cell flow cytometry)
[0065] No cytotoxicity and reliable biocompatibility are the basic requirements for biomaterials to be applied to the human body. Since the application scenario of CaSi2 is the human oral cavity, we chose human oral keratinocytes (HOK) as the cell model for cytotoxicity evaluation experiments. In this study, HOK cells were co-cultured with CaSi2 for 24 hours. Live-dead staining images of HOK cells co-cultured with CaSi2 are shown in Figure 2. Figure 6 As shown, green represents live cells and red represents dead cells. Obviously, the proportion of live cells in all groups with concentrations of 5 mg / mL and below is higher. Cell flow cytometry results ( Figure 7 , Figure 8 ) showed that at a concentration of 5 mg / mL, CaSi2 began to show no cytotoxicity. It was confirmed that CaSi2 with a concentration less than or equal to 5 mg / mL had good biocompatibility with HOK cells.
[0066] 7. Escherichia coli and Staphylococcus aureus experiments (bacterial plate count, SEM)
[0067] Based on its excellent photothermal conversion efficiency and cyclic stability, we further studied the PTT ability of CaSi2. First, the antibacterial ability of CaSi2 was determined by the plate coating method. A 5 mg / ml CaSi2 aqueous solution was used to compare the colony formation of Escherichia coli and Staphylococcus aureus in the absence of light and with light irradiation. Fig. 9 , 10 As shown in the figure, in the absence of light, the growth of the two bacteria was slightly inhibited, and when there was light, there was almost no bacterial growth on the culture plate. In addition, since biofilms are formed by the accumulation and excretion of extracellular substances by bacteria, which enhances the virulence and drug resistance of bacteria, we further evaluated the ability of CaSi2-mediated PTT to eliminate biofilms. After illumination, CaSi2 caused morphological distortion, collapse, and membrane fusion of Escherichia coli and Staphylococcus aureus ( Fig. 9 ). This indicates that CaSi2-mediated PTT can effectively remove bacteria from biofilms. In summary, the antibacterial effect of CaSi2 under dark conditions is weak, and the effect of PTT on bacterial biofilms makes CaSi2 a useful tool for effectively removing bacterial biofilms and a promising candidate for the treatment of periodontitis.
[0068] 8. Analysis of hydrogen production performance of CaSi2 tooth powder
[0069] The hydrogen production performance of the CaSi2 tooth powder prepared in Example 1 was quantitatively evaluated by gas chromatography, the experimental temperature was 10°C, the gas chromatograph model was Furley 97Plus, the detector was a thermal conductivity detector (TCD), the light source power was a 300W xenon lamp, the spectral range was simulated sunlight, the distance between the light source and the reactor was 2cm, the carrier gas type was high-purity argon, and the experimental conditions were 5mg / ml catalyst. Fig.11 As shown in the figure, comparing the production and generation rate of H2 under light and dark conditions, the generation rate of reaction products under light conditions is significantly accelerated and the production increases, indicating that light promotes the hydrogen production reaction.
[0070] 9. Analysis of hydrogen release behavior mechanism
[0071] Specifically, it is divided into the CaSi2 group before reaction (CaSi2), the CaSi2 group after reaction with water under no light conditions (CaSi2-H2O-Dark), and the CaSi2 group after reaction with water under light conditions (CaSi2-H2O-Light).
[0072] XPS results show the changes in the element composition and chemical valence state of each group. Fig.12 As shown in (a), after CaSi2 reacts with water, the overall XPS peak increases, especially under light conditions, which is more significant. This may be because the products after the reaction increase, or the light excites the material to produce more electron-hole pairs, which enhances its conductivity. XPS-C1s spectrum ( Fig.12 In (b), the OC=O peak of CaSi2 after reaction with H2O shifts to the lower energy level, indicating that the carbonyl group forms a hydrogen bond with the hydroxyl group (-OH) in water, which indirectly explains the hydration reaction process of CaSi2. The relationship between the change of the state of elements such as Si and Ca and the release of hydrogen after the hydration reaction is then analyzed. XPS-Si2p spectrum ( Fig.12 In (c), the XPS peak area ratio represents the relative content of elements on the surface of the material. By processing the XPS-Si2p data of CaSi2 before and after the reaction through Avantage, the peak area ratio of each group can be obtained:
[0073] CaSi2:Si2p(oxide):Si2p3 / 2 and Si2p1 / 2component=1:0.38
[0074] CaSi2-H2O-Dark: Si2p(oxide):Si2p3 / 2 and Si2p1 / 2component=1:0.15
[0075] CaSi2-H2O-Light: Si2p(oxide):Si2p3 / 2 and Si2p1 / 2component=1:0.09
[0076] After the reaction with H2O, the relative area of the mixed peaks of Si2p3 / 2 and Si2p1 / 2 of CaSi2 decreased, and the relative area of the peak of Si2p (oxide) increased. This is due to the oxidation of Si atoms (by OH in water). - Provided). The relative area of the mixed peak under light is smaller, so light can accelerate the oxidation of Si atoms. At the same time, the XPS-Ca2p spectrum ( Fig.12 The peak shift in (d) is weak. It can be further considered that the Ca-Si bond is cut by the formation of Si-O bond, and some Ca atoms are dissolved in pure water.
[0077] In electron capture experiments, Fig.13 As shown in the figure, under the same lighting conditions, the hydrogen production of CaSi2 decreases with the increase of potassium dichromate concentration. This indicates that potassium dichromate captures electrons, weakening the electron transfer process between CaSi2 and water, thereby reducing the hydrogen production. The hydrogen production of CaSi2 is higher under light conditions than under no light conditions, indicating that light excitation produces more active electrons.
[0078] The results of electron paramagnetic resonance (EPR) Fig.14 ) not only reconfirmed the existence of electron-hole pairs, but more importantly explained the role of electrons and holes in the release of hydrogen in the photocatalytic reaction, and revealed its participation path. The EPR signal intensity under illumination conditions is lower than the signal intensity under dark conditions as a whole. Under dark conditions, the electron spin state inside the material is mainly affected by its own structure. Without the interference of external light excitation, relatively stable holes are more easily captured by specific capture sites, resulting in a stronger EPR signal. Under illumination conditions, the energy of photons may cause some electrons to transition to higher energy levels, changing the electron distribution inside the material, thereby suppressing the electron spin resonance behavior (photogenerated electrons and hole pairs recombine during the migration process), resulting in reduced signal intensity and reduced fluctuations.
[0079] The simulation calculations were carried out with the help of Density Functional Theory (DFT) and Time-Dependent Density Functional Theory (TD-DFT). CaSi2 was modeled based on literature and XRD characterization data, and all calculations were performed at one atmosphere and 298.15K. The CP2K software package was used for DFT and TD-DFT calculations, and its calculation results can be used as the basis for analyzing molecular orbital transitions. For example, the molecular orbital changes of the catalyst before and after illumination were calculated by CP2K to infer the possible electronic transition process. The excited state wave function obtained by TD-DFT calculation was read by Multiwfn for electron-hole analysis. The molecular structure was displayed in the form of a three-dimensional model through the visualization of Visual Molecular Dynamics (VMD). The results of three different transitions of the main molecular orbitals are shown in Table 1. It can be seen that the first transition is a dominant molecular orbital transition. This shows that in the electronic excitation process of CaSi2, the direct transition from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO) is almost the main pathway. The smaller HOMO-LUMO energy gap indicates that CaSi2 is relatively easy to undergo electronic transitions, so CaSi2 may show higher activity or sensitivity in some chemical reactions or photophysical processes related to electron transfer. VMD visualization results are shown in Figure 2. Fig.15 As shown, copper is Ca, yellow is Si, isovalue = 0.05. The hole-electron analysis results of CaSi2 have three states, as shown in Table 2. The third state has the highest excitation energy and the largest number of molecular orbital pairs, indicating that electrons may transition to molecular orbitals that are farther away from the original HOMO and have higher energy, thereby producing a complex hole-electron distribution. This further shows that CaSi2 has stronger chemical reactivity or more complex photophysical processes in this excited state. The VMD visualization results are shown in Fig.16 As shown in (charge density difference, isovalue 0.001), it can be seen that the reaction between CaSi2 and water is a typical charge transfer excitation process, because holes and electrons are distributed on obviously different atoms. And the excited electrons are concentrated on Si, it can be inferred that the Si site is involved in the generation of H.
[0080] Table 1 Three different transition results of main molecular orbitals
[0081]
[0082] Table 2 Analysis results of three states of holes and electrons in CaSi2
[0083] Serial number Excitation energy (eV) Spin multiplicity Molecular orbital pairs 1 0.051 1 7 2 0.172 1 8 3 0.328 1 17
[0084] 10. Evaluation of the intracellular anti-inflammatory properties of CaSi2 tooth powder
[0085] In the pathogenic progression of periodontitis, dental plaque microorganisms are the initial factors of periodontitis, and the host immune response determines the process of periodontal tissue destruction. Macrophages are basic elements of the host innate immune system. They are key components of the periodontal immune microenvironment and actively participate in the physiological and pathological processes of periodontal tissues. Oxidative stress-related indicators such as Fig.17 As shown, the fluorescence intensity reflects the content of ROS and H2O2 in each group of RAW264.7, respectively. The higher fluorescence intensity of the normal group means that cells may face a certain degree of oxidative stress under normal conditions. Without special intervention, cells can be in a certain inflammatory stress state or have a relatively high risk of inflammation. The fluorescence expression of cells in the CaSi2 material group was reduced, and the level of intracellular oxidative stress decreased, that is, CaSi2 played an anti-inflammatory role. An in vitro cell model of inflammation was further established by stimulating RAW264.7 cells with lipopolysaccharide (LPS). LPS polarized RAW264.7 macrophages to the pro-inflammatory M1 type, such as Fig.18 As shown, CaSi2 can induce M1-type RAW264.7 into the anti-inflammatory M2 type.
[0086] 11. In vivo treatment of periodontal inflammation
[0087] Periodontitis is a highly prevalent infectious and inflammatory disease caused by the accumulation of pathogenic bacteria. Alveolar bone loss is an important clinical manifestation of periodontitis and the main cause of tooth loss in adults. To explore the role of CaSi2 in the treatment of periodontitis in vivo, we constructed a ligature-induced mouse periodontitis model to evaluate the periodontal bone loss and repair and the therapeutic effect of periodontitis. Micro-CT and histological staining were used to explore the therapeutic effect of CaSi2 on alveolar bone loss in experimental periodontitis. Fig.19 Detailed steps from animal model construction to intervention are provided. Briefly, mice were divided into five groups: normal (NC), periodontitis (PD), periodontitis + water under light (PD+Lt.), periodontitis + CaSi2 (PD+CS2), and periodontitis + CaSi2 + light (PD+CS2+Lt.). The maxillary second molars of mice were ligated for 3 weeks to allow pathogen accumulation and inflammatory response, and then received different treatments for 1 week (once in the morning and once in the evening, three minutes each time).
[0088] The changes in alveolar bone were detected by micro-computed tomography (Micro-CT). Micro-CT images showed that the PD group had significant periodontal bone loss compared with the NC group, that is, the distance between the cement-enamel junction and the alveolar bone ridge (CEJ-ABC) became longer, indicating that the model was successfully constructed. Light therapy alone failed to completely rescue the bone loss after ligation. Importantly, we observed that the CEJ-ABC distance was significantly reduced in the PD+CS2 and PD+CS2+Lt. groups compared with the PD group, indicating an improvement in alveolar bone resorption ( Fig. 20 ). Further analysis of specific indicators reflecting the status of alveolar bone ( Fig.21 ), bone mineral density (TMD), bone volume fraction (BV / TV), trabecular number (Tb.N), and trabecular connection density (Conn.D) in each group showed the same trend, which not only indicated that the mouse periodontitis model was successfully established and there was a potential pathophysiological mechanism, but also that the effects of treatment factors on alveolar bone were multi-dimensional and in the same direction, suggesting that the treatment mechanism worked at multiple levels. Compared with the PD group, the PD+CS2 group had a certain effect on trabecular bone-related parameters, was able to restore its number and density, and improved the mechanical properties of alveolar bone. This may be because Ca 2+ However, the parameters of the PD+CS2+Lt. group and the NC group were basically similar, indicating that a large amount of H2 can effectively treat periodontitis at multiple levels, and combined with Ca 2+ Promotes bone repair.
[0089] H&E staining of the maxillary second molars in the PD+CS2+Lt. group showed a decrease in alveolar bone loss (e.g. Fig. 22 (a) shows that the gingival tissue is similar to healthy tissue. In contrast, the other groups not only did not improve the alveolar bone loss, but even showed worm-like resorption of cementum and loss of epithelial papillae. In addition, Masson staining further showed the destruction of fibers and bones after ligation (as shown in Fig. 22 (b) ), PD+CS2+Lt. processing can effectively reconstruct.
[0090] NF-κB (nuclear factor κB) is a key transcription factor that plays a core role in the regulation of inflammatory responses. In periodontitis, stimuli such as bacterial products and inflammatory cytokines can activate the NF-κB signaling pathway. Activated NF-κB enters the cell nucleus and regulates the gene expression of important pro-inflammatory cytokines such as TNF-α (tumor necrosis factor-α) and IL-1β (interleukin-1β). TNF-α and IL-1β then promote the activation, proliferation and chemotaxis of inflammatory cells, thereby continuously amplifying the inflammatory response, ultimately causing inflammation and damage to periodontal tissues. Nrf2 (nuclear factor E2-related factor 2) is an extremely important intracellular antioxidant stress transcription factor, and HO-1 (heme oxygenase-1) is a core antioxidant enzyme downstream of Nrf2. In the local inflammatory microenvironment caused by periodontitis, the antioxidant system composed of Nrf2 and its downstream HO-1 balances the inflammatory response dominated by NF-κB by exerting antioxidant and anti-inflammatory effects, thereby maintaining cell stability and health. However, the expression of HO-1 usually increases significantly when cells face greater oxidative stress. At the same time, the role of the Nrf2 / HO-1 pathway in the analgesic activity of HRW systemic or local administration has been confirmed. To further evaluate the level of expression of related factors in tissues, we performed immunohistochemical staining. Positive cells were identified with brown-yellow markers. The PD group and PD+Lt. group showed significant immunolabeling of NF-κB, TNF-α, and IL-1β signals, while the PD+CS2 group and PD+CS2+Lt. group showed significantly reduced immunolabeling ( Fig.23 ), indicating that CS2 treats periodontal inflammation. Compared with other groups, the PD+CS2+Lt. group had significantly increased immunolabeling of Nrf2 signals. This shows that a large amount of H2 stimulates the transfer of Nrf2 transcription factors from the cytoplasm to the nucleus, thereby alleviating oxidative stress or inflammatory response in cells. At the same time, hydrogen therapy has alleviated oxidative stress to a certain extent, and cells may not need to respond by expressing a large amount of HO-1. Therefore, the expression levels of HO-1 signal immunolabeling in the PD+CS2 group and the PD+CS2+Lt. group are relatively low. This further shows that this hydrogen treatment method can reduce inflammatory pain. The positive areas of various inflammatory-related factors, such as Fig.24 shown.
[0091] 12. Evaluation of tooth remineralization performance in vitro
[0092] The outermost layer of teeth is enamel. In addition to the "corrosive" effect of acidic substances that damages enamel, the acid produced by bacteria decomposing sugars in saliva can also dissolve hydroxyapatite in enamel, causing tooth demineralization. 2+It can effectively promote the deposition of hydroxyapatite minerals on the tooth surface, thereby repairing demineralized tooth enamel and protecting healthy tooth enamel from acid erosion. In vitro remineralization experiments were conducted on acid-eroded teeth at different periods in a simulated oral environment, and the tooth surface morphology at each stage was observed using a scanning electron microscope ( Fig.25 ), EDS analysis of the elemental composition of the tooth surface at each stage, and comparison of the atomic ratio of Ca and P (At Ca / At P )( Fig.26 The results show that the surface of the unetched teeth is smooth, satisfying the Ca / P atomic ratio of hydroxyapatite of approximately 1.67, while the surface of the etched teeth is loose and porous, At Ca / At P The ex vivo human teeth were brushed with CaSi2 in simulated oral saliva. After 1 day, the surface was still loose and porous, close to the surface morphology of the teeth after acid etching, but there was obvious accumulation of particles on the surface. Ca / At P The ratio becomes larger; at 3 and 7 days, the tooth surface gradually becomes flat, close to the normal tooth surface morphology before acid etching, and At Ca / At P The results are close to those of unetched teeth. This indicates that the products of the hydration reaction of CaSi2 materials can be effectively deposited on the surface of the enamel sheet, and hydroxyapatite is produced in the process, thus achieving the remineralization of teeth.
[0093] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for preparing a tooth powder for periodontal antibacterial and anti-inflammatory effects and tooth remineralization, characterized in that: The method comprises the following steps: S100: grinding Ca powder and Si powder and then calcining for the first time, naturally cooling, adding Si powder to the first calcined product, repeating the grinding step, and then calcining for the second time, wherein the grinding and calcining processes are both carried out under an inert gas protective atmosphere; S200: After the second calcined product is cooled naturally, impurities are removed by washing, and then ball milled in a sealed environment for 100 minutes; S300: After subjecting the ball milled product to ultrasonic and centrifugal treatment, the supernatant is collected and centrifuged again, and then dried to obtain tooth powder.
2. The method for preparing the tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 1, characterized in that: The mass ratio of the Ca powder to the Si powder is 10:
7.
3. The method for preparing the tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 2, characterized in that: The mass of Si powder added to the first calcined product is 2.43 times the mass of the first calcined product.
4. The method for preparing the tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 1, characterized in that: The grinding step in S100 specifically includes: first grinding for 30 minutes, and then adding anhydrous ethanol and further grinding for 10 minutes.
5. The method for preparing the tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 1, characterized in that: The first calcination in S100 is calcined at 1000° C. for 5 min, and the second calcination is calcined at 1000° C. for 10 h.
6. The method for preparing the tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 1, characterized in that: The sealing environment described in S200 is to add anhydrous ethanol for liquid sealing.
7. The method for preparing the tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 1, characterized in that: The ultrasonic and centrifugal treatment process of the ball milling product in S300 specifically includes: ultrasonicating the ball milling product in an ice bath for 1.5 hours, then centrifuging at 3000 rpm for 10 minutes, collecting the supernatant, and then centrifuging at 12000 rpm for 20 minutes.
8. The method for preparing the tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 1, characterized in that: The drying temperature in S300 is 50° C. and the drying time is 24 hours.
9. A tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. The tooth powder for periodontal antibacterial and anti-inflammatory and tooth remineralization according to claim 9, characterized in that: The tooth powder is nano-CaSi2 powder.